(untitled) (Research, Society and Development, 2022)
The study aims to describe the experiences of the specific axis in an oncology Surgical Center. Methodologically, it is a descriptive study, of the experience report type, developed by a resident nurse in an oncology surgical clinic at the State University of Pará working in a reference hospital in oncology in the north of the country. The Uniprofessional residency program organizes the activities developed by resident nurses according to the classification of their specialties, forming their specific axes. For those working in the oncology surgical clinic, one of the axes is the setting of the surgical center where their activities last for two months. Specific procedures could be witnessed by the resident, such as the sentinel lymph node survey, a procedure that allows the evaluation of the lymph node staging of a certain region. tissues, a technique developed by the pathologist of the sector. This report took place in the months of October and November 2021. In conclusion, it was noticed through the practice as a nursing resident the relevance of his work in a critical sector, it is of great value for the construction of his professional life the experience with this profile of clientele, and with the incentive and fair training, its protagonism certainly goes beyond expectations.